Development and proposed evaluation of an eHealth learning tool for undergraduate university students in Ireland. - Darker, Catherine D; Moore, Emma; Flynn, Ellen; O'Neill, Mary; Doherty, Lena; McMahon, Jean; McLoughlin, Orla; Rouine, Eimear; Ivers, Jo-Hanna; Allwright, Shane; McGrath, David; Seery, Aidan; et al. (Health Promotion International, 2022)
Undergraduate university students are at a critical stage of development in terms of their academic, social, psychological and behavioural health. Patterns established during these formative years can last a lifetime. eHealth tools have the potential to be engaging, convenient and accessible to a wide range of students by providing health information and enhancing the uptake of positive health behaviours. The 'Healthy Trinity Online Tool' (H-TOT) was developed in collaboration with students and a transdisciplinary team with decades of experience between them in terms of research, clinical responsibility and service delivery. Developmental steps undertaken included: a literature review to formulate the topic content choices; a survey of students to check the relevance and suitability of topics identified; and, the tacit experience of the development team. This co-design model led to the development of content encompassing academic life, healthy eating, physical activity, mood, financial matters, alcohol, tobacco, drugs and relaxation. Qualitative focus groups were subsequently conducted for in-depth exploration of the usage and functionality of H-TOT. The theoretical underpinnings include the locus of control and social cognitive theory. Evidence-based behavioural change techniques are embedded throughout. During early pre-piloting of H-TOT, the team identified and solved content functionality problems. The tone of the content was also revised to ensure it was non-judgemental. To make the H-TOT as interactive as possible, video scenarios were included and all content was audio-recorded to allow playback for students with visual or learning difficulties. Evaluation plans for the pilot year of H-TOT are outlined.